Mapping of Flooded Areas in the Kudus District - Rina Fiati; Anastasya Latubessy (Institute of Advanced Engineering and Science, 2016)
Flood is still an annual problem in the Kudus District. Based on the survey and interview with Regional Disaster Management Agency (BPBD – Badan Penanggulangan Bencana Daerah) data showed that in the Kudus District there are still many flood-prone areas. They also said that, there are six parameter that can be used to identify potential flood area such as: extensive inundation (km2, ha), depth or height of flood waters (meters), the flow velocity (m/s,km/h), the material washed away by flood flow (rocks, boulders, trees, and other solid objects), concentrations of water or silt thickness (meters, centimeters), and duration of inundation (hours, days, months). Therefor this research use six parameters are then analyzed and used as a benchmark model to identify flood-prone areas by using the production rule method, and as the material in constructing and designing flood-prone area identification systems based on expert system. Thus this research resulted a system to assist the identification of flood prone areas in the Kudus District by using expert system and geographic information system (GIS).